Determination Of Polysaccharide From 'Cendawan Busut' Crude Water Extract - Ahmad Nabil Eshamudin; Mohd Redza Riquelme Nisham; Srivani Sellathoroe; Rahayu Ahmad; Ehwan Ngadi (Universiti Sains Islam Malaysia, 2024)
Junior Researcher International Conference (iJURECON) Kolej Genius Insan (KGI) 17 dan 18 November 2020 Pages : 245-248